PENDAMPINGAN KESADARAN LINGKUNGAN UNTUK MENINGKATKAN SIKAP DAN PERILAKU MAHASISWA - Jahroni; Misbachul Munir; Maya Febianti; Eli Retnowati; Utami Puji Lestari (Jurnal Pengabdian Masyarakat Sabangka, 2026)
Environmental problems are fundamentally rooted in human behavior; therefore, changes in attitudes and awareness are key to achieving environmental sustainability. Higher education institutions play a strategic role in fostering environmental awareness among students. This Community Service Program (PKM) aims to enhance students’ environmental awareness and pro-environmental behavior through a Participatory Action Research (PAR) approach. The PAR method actively involves students in all stages of the program, including planning, implementation, and evaluation. The activities conducted consisted of environmental hygiene socialization, campus area clean-up activities, organic waste management, and the planting of ornamental plants and family medicinal plants (TOGA). The results indicate an increase in student participation, responsibility, and concern for environmental cleanliness and sustainability within the campus environment. Although students’ environmental knowledge remains at a moderate level, the program successfully fostered collective awareness and positive environmental behavior. This assistance program is expected to serve as a sustainable initiative in developing a clean, healthy, and environmentally friendly campus culture.